Pendampingan Perencanaan Desain Gedung Olahraga Desa Gogik Kecamatan Ungaran Barat - Riza Susanti; Previari Umi Pramesti (Sekolah Vokasi Universitas Diponegoro, 2021)
Sport is one of the most important needs for humans. Gogik Village is one of the villages where people are classified as fond of sports. However, one of the obstacles faced by Gogik Village is the absence of a standardized sports hall that can be used to facilitate activities for the people of Gogik Village. This is the background of this community service activity to help the people of Gogik Village in planning the design of a sports building (GOR) which can later be used as one of the village facilities. Based on the survey results, it was found that the needs of the people of Gogik Village for a sports building (GOR) which at least can be used as a volleyball court, basketball and futsal court. With reference to this as well as the availability of land and applicable regulations, it is determined that the design of the sports building in Gogik village will be included in the type C classification by referring to SNI 03-3647-1994.